BASIC DESIGN OF OUTPUT WITH MEDIATOR PROGRAMMABLE PERIPHERAL INTERFACE USING LANGUAGE C 8255 - Syamsudin Syamsudin; Nenny Anggraini, SKom.,MT (Jurnal Sistem Komputer, 2005)
Series of "Basic Design of Intermediary Output With Programmable Pheriferal 8255 Interface Using C Language", is a series composed of PCs, interface 8255, and the basic module output circuits that are interconnected with one another. In 8255 PPI for the liaison function between the computer with a basic circuit of output circuit is useful for displaying the output of the LED display.